الذكاء الوجداني وأساليب مواجهة الضغوط لدى طلبة الجامعة ذوي خبرات الإساءة في مرحلة الطفولة - أحمد، عادل سيد عبادي (جامعة البحرين - مركز النشر العلمي, 2017)
Exposure to abuse in childhood leaves continuing effects on the individual's character. These effects appear in the individual's inner feelings and his/her response to situations. Thus, the present study aimed at investigating the differences between the high and low levels of childhood abuse experiences in the emotional intelligence, arrangement of the abuse experiences, coping styles, and the relationship between them among students with childhood abuse experiences. Moreover, the present study aimed at identifying the predictability of coping styles in light of emotional .intelligence Tools of the study included the Emotional Intelligence Scale (prepared by A1 Khouly, 2002), Coping Styles Scale (prepared by the researcher), and the Scale of Childhood Abuse Experiences (prepared by Mukhaimar & Abdel-Razek, 2011). Participants were 140 university students (males and females). Findings revealed that there were differences among normal students and those with childhood abuse experiences in emotional intelligence. Also, there was a relationship between emotional intelligence and coping styles among the students with childhood abuse experiences. In addition, psychological abuse and negative coping styles were most frequently used by students with childhood abuse experiences. Furthermore, it was possible to predict the coping styles in light of the emotional intelligence. Finally, the researcher presented some suggestions and recommendations, which showed the scientific and practical significance of the current study in higher education.
التعرض للإساءة في مرحلة الطفولة يترك تأثيرات مستمرة على شخصية الفرد تظهر في مشاعره الداخلية واستجابته للمواقف، ومن هنا فقد هدفت الدراسة الحالية إلى معرفة الفروق بين الطلبة المرتفعين والمنخفضين ذوي خبرات الإساءة في مرحلة الطفولة في الذكاء الوجداني، وترتيب خبرات الإساءة وأساليب المواجهة والعلاقة بينهما لدى طلبة ذوي خبرات الإساءة في مرحلة الطفولة، والتنبؤ بأساليب مواجهة الضغوط بمعلومية الذكاء الوجداني. وتمثلت أدوات الدراسة مقياس الذكاء الوجداني (إعداد الخولي، 2002)، ومقياس أساليب مواجهة الضغوط (إعداد الباحث)، ومقياس خبرات الإساءة في مرحلة الطفولة (إعداد مخيمر وعبد الرازق، 2011)، وقد تكونت عينة الدراسة من 140 طالبا وطالبة. وأسفرت النتائج عن وجود فروق بين الطلاب العاديين وذوي خبرات الإساءة في مرحلة الطفولة في الذكاء الوجداني، ووجود علاقة بين الذكاء الوجداني وأساليب المواجهة لدى الطلبة ذوي خبرات الإساءة في مرحلة الطفولة، كذلك مثلت الإساءة النفسية وأساليب المواجهة السلبية الأكثر استخداما من الطلبة ذوي خبرات الإساءة في مرحلة الطفولة، كذلك فقد أمكن التنبؤ بأساليب مواجهة الضغوط بمعلومية الذكاء الوجداني، وقد تم في ضوء مناقشة هذه النتائج وضع بعض المقترحات والتوصيات التي أوضحت الفائدة العلمية والتطبيقية للدراسة الحالية في مرحلة التعليم الجامعي.
Keywords: الضغوط النفسية; الذكاء الوجداني; طلبة الجامعة; علم النفس التربوي